THE RELATIONSHIP BETWEEN FLAVONOIDS AND CANCER - Al anisi, Ayam; Hami, Hasan Jasim; Barrak, Mohammed M. (Journal of Medical Genetics and Clinical Biology, 2024)
Flavonoids are the effective ingredients of the compounds found in grains, vegetables, fruits, seeds and some drinks that have medicinal, free radical reducing and anti-cancer functions. In plants, flavonoids play an important role in multiple functions including color formation, growth, and protection against damage and microorganisms. Articles have stated that the molecular functions of flavonoids may improve health and reduce disease symptoms, reduce antibiotic resistance and reduce inflammation in humans. One of the features of such research is the potential effect of flavonoids on cancer risk.Chemically, flavonoids have an overall 15-carbon skeletal structure consisting of two phenyl rings and one heterocyclic ring. This carbon structure can be abbreviated as C6-C3-C6. Flavonoids are the effective ingredients of the compounds found in grains, vegetables, fruits, seeds and some drinks that have medicinal, free radical reducing and anti-cancer functions. In plants, flavonoids play an important role in multiple functions including color formation, growth, and protection against damage and microorganisms. Articles have stated that the molecular functions of flavonoids may improve health and reduce disease symptoms, reduce antibiotic resistance and reduce inflammation in humans. One of the features of such research is the potential effect of flavonoids on cancer risk.